2000
DOI: 10.1038/sj.bmt.1702697
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-leukemia-induced complete remission following unrelated umbilical cord blood transplantation for acute leukemia

Abstract: Summary:A 15-year-old female received an unrelated three of six HLA antigen matched umbilical cord blood (UCB) transplant for refractory, relapsed T-cell ALL. Conditioning consisted of TBI, melphalan, and anti-thymocyte globulin (ATG), with cyclosporin A (CsA) and solumedrol for GVHD prophylaxis. She engrafted and a day 34 bone marrow aspirate showed 100% donor cells and no evidence of leukemia. The post-transplant course was complicated by mild grade I acute GVHD involving skin, and limited chronic GVHD of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…From the present clinical experience it is clear that, despite the decreased incidence and severity of GvHD associated with UCB grafts, GvL immunologic effects are maintained [34]. Clinical reports of allogeneic UCB recipients have not identified increased relapse rates [7][8][9]14,15].…”
Section: Ucb Basic Biology and Implications For The Development Of Gvmentioning
confidence: 99%
“…From the present clinical experience it is clear that, despite the decreased incidence and severity of GvHD associated with UCB grafts, GvL immunologic effects are maintained [34]. Clinical reports of allogeneic UCB recipients have not identified increased relapse rates [7][8][9]14,15].…”
Section: Ucb Basic Biology and Implications For The Development Of Gvmentioning
confidence: 99%
“…Another indirect observation suggesting the presence of GVT activity after UCB transplantation is highlighted by a patient with acute lymphoblastic leukemia who suffered a relapse after transplantation but reentered complete remission after withdrawal of immunosuppression [81]. It is also notable that in one study, only 4 (8%) of 48 patients with CML suffered relapse after UCB transplantation [25].…”
Section: Disease Relapse and Graft-versus-leukemia Activitymentioning
confidence: 97%
“…Because donor leukocytes are not available after UCB transplantation from unrelated donors, alternative strategies for augmenting GVT and antiviral activity should be considered. Suggested approaches include IL-2 augmentation of natural killer cell-mediated cytotoxicity, ex vivo expansion and activation of UCB T-cells, and employment of dendritic cell vaccines designed to stimulate the immune response against neoplastic cells [93][94][95][96].…”
Section: Disease Relapse and Graft-versus-leukemia Activitymentioning
confidence: 99%
“…1,2 Howrey et al 8 reported that discontinuation of CYA, and G-CSF administration generate a GVL effect, which can be powerful enough to induce complete remission in patients who relapse after UCBT. Immunotherapy is not always durable, and relapse continues to occur very late.…”
Section: Discussionmentioning
confidence: 99%